Wheat belly : lose the wheat, lose the weight, and find your path back to health - Davis, William, 1957- (Rodale : Distributed to the trade by Macmillan, 2011)
A renowned cardiologist explains how eliminating wheat from our diets can prevent fat storage, shrink unsightly bulges, and reverse myriad health problems.